Physiological response to drought stress in Camptotheca acuminata seedlings from two provenances - Ying, Ye Q.; Song, Li L.; Jacobs, Douglass F.; Mei, Li; Liu, Peng; Jin, Song H.; Wu, Jia S. (Frontiers in Plant Science, 2015)
Drought stress is a key environmental factor limiting the growth and productivity of plants. The purpose of this study was to investigate the physiological responses of Camptotheca acuminata (C. acuminata) to different drought stresses and compare the drought tolerance between the provenances Kunming (KM) and Nanchang (NC), which are naturally distributed in different rainfall zones with annual rainfalls of 1000-1100 mm and 1600-1700 mm, respectively. We determined relative water content (RWC), chlorophyll content (Chl(a+b)), net photosynthesis (Pn), gas exchange parameters, relative leakage conductivity (REC), malondialdehyde (MDA) content and superoxide dismutase (SOD) and peroxidase (POD) activities of C. acuminata seedlings under both moderate (50% of maximum field capacity) and severe drought stress (30% of maximum field capacity). As the degree of water stress increased, RWC, Chl(a+b) content, Pn, stomatal conductance (Gs), transpiration rate (Tr) and intercellular CO2 concentration (Ci) values decreased, but water use efficiency (WUE), REC, MDA content and SOD and POD activities increased in provenances KM and NC. Under moderate and severe drought stress, provenance KM had higher RWC, Chl(a+b), Pn, WUE, SOD and POD and lower Gs, Tr, Ci and REC in leaves than provenance NC. The results indicated that provenance KM may maintain stronger drought tolerance via improvements in water-retention capacity, antioxidant enzyme activity and membrane integrity.